Study protocol: randomised controlled trial evaluating exercise therapy as a supplemental treatment strategy in early multiple sclerosis: the Early Multiple Sclerosis Exercise Study (EMSES). Issue 1 (12th January 2021) - Riemenschneider, Morten; Hvid, Lars G; Ringgaard, Steffen; Nygaard, Mikkel K E; Eskildsen, Simon F; Petersen, Thor; Stenager, Egon; Dalgas, Ulrik
Abstract : Introduction: In the relapsing remitting type of multiple sclerosis (MS) reducing relapses and neurodegeneration is crucial in halting the long-term impact of the disease. Medical disease-modifying treatments have proven effective, especially when introduced early in the disease course. However, patients still experience disease activity and disability progression, and therefore, supplemental early treatment strategies are warranted. Exercise appear to be one of the most promising supplemental treatment strategies, but a somewhat overlooked 'window of opportunity' exist early in the disease course. The objective of this study is to investigate exercise as a supplementary treatment strategy early in the disease course of MS. Methods and analysis: The presented Early Multiple Sclerosis Exercise Study is a 48-week (plus 1-year follow-up) national multicentre single-blinded parallel group randomised controlled trial comparing two groups receiving usual care plus supervised high-intense exercise or plus health education (active control). Additionally, data will be compared with a population-based control group receiving usual care only obtained from the Danish MS Registry. The primary outcomes are annual relapse rate and MRI derived global brain atrophy. The secondary outcomes are disability progression, physical and cognitive function, MS-related symptoms, and exploratory MRI outcomes. All analyses will be performed as intention to treat. Ethics and dissemination: The study is approved by The Central Denmark Region Committees on Health Research Ethics (1-10-72-388-17) and registered at the Danish Data Protection Agency (2016-051-000001 (706)). All study findings will be published in scientific peer-reviewed journals and presented at relevant scientific conferences. Trial registration number: NCT03322761 .